2013
DOI: 10.9779/puje583
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Education Supervisors in Turkey

Abstract: ÖzetBu araştırmanın amacı, müfettişlerin demografik ve sosyo-ekonomik özelliklerini, yaşam ve tüketim alışkanlıklarını, akademik niteliklerini ortaya koymak; toplumsal, ekonomik, siyasal ve mesleksel konulardaki görüşlerini belirlemektir. Araştırma tarama modelindedir. Çalışmanın örneklemini 651 denetmen oluşturmaktadır. Veri toplama aracı olarak 39 sorudan oluşan bir anket kullanılmıştır. Denetmenler, çoğunlukla Türk Halk Müziği dinlemektedirler. En çok okudukları kitap türü, romandır. Yıllık izinlerini daha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Similar results were also reported by Demir (2013), who acknowledged that students could learn positive or negative behaviors by taking nonteaching staff as models. Several studies also handled the auxiliary staff and their functions in the education system and concluded that auxiliary staff is unqualified (Ertör & Akan, 2016), do not have adequate knowledge about preschool education (Tok, 2002), and should be caring and establishing good relations with students (Acun & Erten, 1993).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar results were also reported by Demir (2013), who acknowledged that students could learn positive or negative behaviors by taking nonteaching staff as models. Several studies also handled the auxiliary staff and their functions in the education system and concluded that auxiliary staff is unqualified (Ertör & Akan, 2016), do not have adequate knowledge about preschool education (Tok, 2002), and should be caring and establishing good relations with students (Acun & Erten, 1993).…”
Section: Literature Reviewmentioning
confidence: 99%